In vitro, in vivo metabolism and quantification of the novel synthetic opioid N-piperidinyl etonitazene (etonitazepipne) - Berardinelli, Diletta; Taoussi, Omayema; Carlier, Jeremy; Tini, Anastasio; Zaami, Simona; Sundermann, Tom R.; Busardò, Francesco Paolo; Auwärter, Volker (Clinical chemistry and laboratory medicine, 2024)
Objectives N-piperidinyl etonitazene (etonitazepipne) is a newly synthesized opioid related to the 2-benzylbenzimidazole analog class. Etonitazepipne has been formally notified and placed under intensive monitoring in Europe in January 2022. Nitazenes have high affinity at µ-opioid receptor (MOR). Etonitazepipne, specifically shows a EC 50 of 2.49nM, suggesting about 50 times higher potency combined with higher efficacy compared to morphine. Antinociceptive potency l (‘hot plate test’ with rats) was 192-fold greater than that of morphine. Methods Here we report on a post-mortem case involving etonitazepipne and its quantification using a standard addition method (SAM) through liquid chromatography tandem mass spectrometry (LC-MS/MS). In addition, characterization and identification of phase I human metabolites using in vitro assay based on pooled human liver microsomes (pHLM) was performed along with the analysis of authentic urine samples by means of high-performance liquid chromatography high-resolution tandem mass spectrometry (LC-HRMS/MS). Results The concentration of etonitazepipne in post-mortem blood and urine was 8.3 and 11ng/mL, respectively. SAM was validated by assessing the following parameters: intraday and interday repeatability, matrix effect and recovery rate in post-mortem blood. A total of 20 and 14 metabolites were identified after pHLM incubation and urine analysis, respectively. Most pronounced in vitro and in vivo transformations were O-deethylation, hydroxylation, ketone reduction, and combinations thereof. Conclusions Considering small traces of the parent drug often found in real cases, the identification of metabolic biomarkers is crucial to identify exposure to this drug. O-deethylated, oxidated metabolites, and combination thereof are proposed as urinary biomarkers along with the parent compound.
Gesehen am 22.07.204